Experimental model of infection by Enterococcus faecalis biofilms in human root canal and dentinal tubules - Martín, Gabriela (2013)
Fil: Martín, Gabriela. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra Endodoncia A; Argentina.